1976
DOI: 10.1007/bf01990204
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal mitochondria in retinoblastoma

Abstract: In examination of six retinoblastoma tumor specimens, bizzare mitochondria were often found. Some are irregular forms with focal expansion and constrictions. Occasionally, a portion of the mitochondria forms rings. Branching mitochondria are also seen. Other striking features of the mitochondria from tumor cells are the alternation of cristae. Dense bodies are also occasionally observed within the mitochondria. Morphological modifications of the mitochondria may be as results of pathological conditions of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A study by Sun [25] has for the first time identified the abnormal mitochondria in six retinoblastoma tumor specimens where they often found bizarre mitochondria. Apart from that ring forms, branching mitochondria were also seen.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Sun [25] has for the first time identified the abnormal mitochondria in six retinoblastoma tumor specimens where they often found bizarre mitochondria. Apart from that ring forms, branching mitochondria were also seen.…”
Section: Discussionmentioning
confidence: 98%

Cancer

Noakes,
Kalamian,
Seyfried
et al. 2023
Ketogenic